ISLAMISASI NUSANTARA: SEJARAH, DINAMIKA POLITIK DAN PERKEMBANGAN SOSIAL-BUDAYA - Maftuh Ajmain (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
This article discusses the process of Islam's entry and development in Indonesia from the early days of maritime contact between the archipelago and the Islamic world to the post-independence period. The study was conducted by examining theories of Islam's arrival, the development of Islamic kingdoms, socio-cultural dynamics, and political changes from the colonial to the modern era. Using a historical approach and document analysis, this paper maps the long journey of Islam as a cultural, social, and political force in Indonesia. This study confirms that the Islamisation of the archipelago took place gradually, peacefully, and adaptively through trade routes, political power, and religious education. The implications of this formed the distinctive character of Indonesian Islam—moderate, pluralistic, and layered according to the social conditions of each region.